Symbolism in Gandrung Dance and Its Preservation Efforts in Kemiren Village, Glagah District, Banyuwangi Regency - Mahfud, Mahfud; Afriani, Imro'atul Husna; Anwar, Syaiful (Nusantara Hasana Berdikari, 2021)
Gandrung is one of the traditional dance arts in the Banyuwangi Regency. Gandrung Banyuwangi dance in the performance there are three parts, namely Jejer Gandrung, ngrepen or repenan, paju or maju Gandrung, and seblang-seblangan. This dance is performed in various events such as circumcision, weddings, tourism events, and in commemoration of the anniversary of the Banyuwangi district city, and is used as local content for the school level. The values ​​contained in the Gandrung dance are the values ​​of struggle, beauty, point of view on life, symbols, culture, and responsibility. Efforts to preserve the Gandrung dance culture so that it does not become extinct are using comprehensive training in schools and studios (Sanggar-sanggar) in Kemiren village, even from kindergarten, elementary to high school. The aims of this study are: (1) to describe the origins of the Gandrung dance, (2) to describe the form in the Gandrung dance movement, (3) to describe the values ​​contained in the Gandrung dance, (4) to describe the efforts to preserve the Gandrung dance. This research is a qualitative descriptive study. To achieve this goal, data were collected using participatory observation, documentation studies, and interviews. The data analysis technique used is an interactive analysis model. The research was conducted in Kemiren village, Glagah sub-district. Banyuwangi district as the object of research is the people of Kemiren village, Gandrung dancers, Kemiren village officials, and the Banyuwangi Culture and Tourism Office. The findings of the study indicate that the origin of the Gandrung dance was started during the colonial period of the Dutch government, where Gandrung was performed by a man named Marsan and replaced by a woman named Temu. The Banyuwangi government even began to oblige every student from elementary to high school to take part in Banyuwangi's Gandrung art extracurricular as an effort to preserve the Gandrung dance. The Banyuwangi Regency Culture and Tourism Office also has a program by actualization which is carried out once a year and its implementation itself at the Gandrung Sewu event. Based on the results of this study, it can be suggested that further research can be carried out, for example, the community understands more about the meaning content contained in each culture owned by the Banyuwangi district and how to maintain and preserve regional culture in a sustainable manner, so it cannot be crushed by the flow of globalization.